"Bring back the salad bar": perceptions of health in rural delta middle school students. Issue 6 (2nd November 2022) - Williams, Natalie; Mann, Georgianna; Cafer, Anne; Evers, Charles; Kaiser, Kimberly
ABSTRACT: This study examined perceptions of healthy eating by middle school students in one low-income rural Mississippi Delta school using 10 focus groups (n = 62). The Social Ecological Model was framework for inductive and deductive thematic coding to analyze transcripts. Results indicated students had a "good food, bad food" approach to health. Students believed the school environment was not conducive to a healthy lifestyle, citing poor food and water quality in addition to a lack of staff. An intervention aimed at increasing self-motivation through school- or community-based initiatives may be successful. Including the community and key stakeholders would improve potential intervention success.